1993
DOI: 10.1002/path.1711700209
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistological study of cutaneous lymphocytes in vitiligo

Abstract: In a study of 49 biopsies from the margins of depigmented cutaneous lesions in 18 patients with vitiligo, highly significant overall increases were found in CD3+, CD4+, and CD8+ T cells, though cell numbers in individual cases were often within the normal range. Many of the T cells were activated (MHC class II+, interferon gamma+), of CD45RO (UCHL1+) memory subset, and many expressed the cutaneous lymphocyte-associated antigen (HECA-452+) typical of skin-homing T cells. Immunohistologically, the most intense e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 16 publications
7
109
0
1
Order By: Relevance
“…A loss of melanocytes has been demonstrated in established vitiligo lesions (5,6). However, melanocyte destruction has never been clearly demonstrated in NSV.…”
Section: Melanocyte Destructionmentioning
confidence: 99%
“…A loss of melanocytes has been demonstrated in established vitiligo lesions (5,6). However, melanocyte destruction has never been clearly demonstrated in NSV.…”
Section: Melanocyte Destructionmentioning
confidence: 99%
“…12,13 Two principal hypotheses concerning the etiology of vitiligo include: (1) the self-destruct model, which suggests that biochemical and/or structural defects inherent to patient melanocytes contribute to the initiation and/or progression of melanocyte cytolysis; and (2) the autoimmune model, which suggests that melanocyte death occurs through inappropriate immune system destruction of pigment cells. 11,14 There is considerable evidence that disease progression in some vitiligo patients involves autoimmune attack of the melanocytes, as evidenced by the presence of both cellular [15][16][17] and humoral [18][19][20] antimelanocyte autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, the in situ data on the role of infiltrating immunocompetent cells in generalized vitiligenous lesions are limited (Abdel-Naser et al, 1994;Badri et al, 1993). We have previously reported that in inflammatory vitiligo, a rare type of depigmentary disease, skin infiltrates of T cells and macrophages around the perilesional (PL) site parallel the development of the lesions in a centrifugal manner (Le Poole et al, 1996).…”
mentioning
confidence: 99%
“…We have previously reported that in inflammatory vitiligo, a rare type of depigmentary disease, skin infiltrates of T cells and macrophages around the perilesional (PL) site parallel the development of the lesions in a centrifugal manner (Le Poole et al, 1996). Although expression of CLA was evaluated in two studies, Badri et al (1993) and Le Poole et al (1996), the importance of CLA ϩ T cell subsets in relation to melanocyte destruction was not explicitly demonstrated by double-label immunohistochemistry. Subsequently, despite these reports, the extent to which local immune response is associated with the development of vitiligo is still debated (Berd et al, 1996), due to the lack of appropriate in vivo studies on the immunopathology of generalized vitiligo.…”
mentioning
confidence: 99%